Development of Mobile-Based Learning Management System in UUM - Abbas, Alaa Sinan (2009)
Mobile technology has incorporated the use of Internet in mobile phones. The convergence of mobile communications and hand-held computers offer the opportunity to develop technology that will assist individuals and groups to learn at anytime and from anywhere (Horng et al, 2007). Wireless Application Protocol (WAP) has combined two of the widest utilised technology today: mobile phones and Internet (Chong, et. a,.2008). This research proposes to improve the 'Learn Care' site in UUM by developing a Mobile-based Learning Management System to enable the lecturers and the students to access the 'Learn Care' site at anytime and from anywhere, using their mobile phones. Most of the lecturers and students already have mobile phones. This can therefore reduce the effort, time and cost and facilitate the interaction between lecturers and students, more easily and effectively, and subsequently lead to the obtaining of better results in education.